"Cult of Equity": Actuaries and the Transformation of Pension Fund Investing, 1948–1960. Issue 2 (15th June 2015) - Avrahampour, Yally
Abstract : This article examines the mid-twentieth-century transformation of U.K. pension fund investment policy known as the "cult of equity." It focuses on the influence exercised by the Association of Superannuation and Pension Funds over actuarial and corporate governance standards, through actuaries who were members of its council. This intervention led to increasingly permissive actuarial valuations that reduced contributions for sponsors of pension funds investing in equities. Increased demand for equities required pension funds to adopt a more permissive approach to corporate governance than insurance companies and investment trusts, and contributed to declining standards of corporate governance.